Efektivitas Kuis dalam Meningkatkan Hasil Belajar IPS Siswa Kelas VI SDN 8 Keruak Kecamatan Keruak Kabupaten Lombok Timur - Jamiluddin Jamiluddin (FONDATIA, 2018)
This study aims to describe the effectiveness of quizzes in improving the learning outcomes of IPS students grade VI SDN 8 Keruak Keruak District East Lombok regency. This study was categorized into experimental research. The population of this study is all students of class VI SDN 8 Keruak amounted to 22 students. The sample of this study consists of two classes, namely the experiment as many as 11 people and control class as many as 11 people. Sample determination is done by using purposive sampling technique. The technique used to collect research data is a test technique. The collected data was analyzed using descriptive statistical technique of t tes type. The results showed that the effective quiz was applied in improving the learning outcomes of IPS students of grade VI SDN 8 Keruak. That is, the quiz is a strategy that can change the process (shaping student learning behavior) and student learning outcomes. This is evident in both research classes. For the control class, students' attitudes and attitudes toward IPS learning are lacking. Unlike experimental class students, students' attitudes and attitudes toward IPS learning are very high. The increase in results appears in the acquisition of the average grade of the experimental class better than the average value of the control class